Polarimetry with the Gemini Planet Imager: Instrument Characterization and Future Science. Issue Volume 8:Issue S299(2013) (6th January 2014) - Millar-Blanchaer, Max; Wiktorowicz, Sloane J.; Perrin, Marshall D.; Graham, James R.; Thomas, Sandrine J.; Dillon, Daren; Fitzgerald, Michael P.; Maire, Jérome; Macintosh, Bruce; Goodsell, Stephen J.
Abstract: The Gemini Planet Imager (GPI) is a high contrast coronagraph designed to directly image exoplanets and circumstellar disks. GPI includes a polarimetry mode designed to characterize dust grains and enhance the contrast of scattered, polarized light by a factor of 100. Reflections and birefringence of optics within the optical train induce a polarization signature that needs to be measured a priori and calibrated out during data reduction. Here we report on the results of an extensive laboratory characterization campaign of the polarimetry mode. The linear instrumental polarization has been measured in 4 GPI passbands and found to be between 3.5 ± 0.3 % at 1.0 micron and 1.1 ± 0.3 % at 2.0 microns. Modulation efficiency has been measured to be 94% at 1.0 micron increasing to 97% at 2.0 microns. Stability has been shown to better than 0.6% over timescales of 3 months and over cool down cycles. The tests show that GPI passes all polarimetry design requirements and should be able to measure circumstellar disk linear polarization to 1% accuracy.